The Presentation of Debrecen University’s Solar Energy Power Plant - Szecskó, Zoltán; Grasseli, Gábor (Acta Agraria Debreceniensis, 2005)
Energy plays an important role in everyday life and in the economy. The use of fossil energy sources greatly damages the environment. Besides this, the quantity of these energy sources is limited. Therefore, it is important to increase the share of renewable energy sources (solar, wind, water, biomass) in energy generation. Huge amounts of energy (1150-1300 kWh/m2) arrive at the earth from the sun, which utilized in passive and active ways. One of the active applications is photovoltaic current production, in the course of which electricity is produced directly with PV-Panels. This can be fed into the grid.